2021
DOI: 10.3389/fphys.2021.764061
|View full text |Cite
|
Sign up to set email alerts
|

Culex quinquefasciatus Late Trypsin Biosynthesis Is Translationally Regulated by Trypsin Modulating Oostatic Factor

Abstract: Trypsin is a serine protease that is synthesized by the gut epithelial cells of female mosquitoes; it is the enzyme that digests the blood meal. To study its molecular regulation, Culex quinquefasciatus late trypsin was purified by diethylaminoethyl (DEAE), affinity, and C18 reverse-phase high performance liquid chromatography (HPLC) steps, and the N-terminal amino acid sequence was determined for molecular cloning. Five overlapping segments of the late trypsin cDNA were amplified by PCR, cloned, and the full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…We observed that AeaTMOF belongs to a family of proline-rich peptides that were shown to act as antimicrobial peptides by inhibiting the translation of proteins by bacterial ribosomes like Oncocin112 [13][14][15]. Therefore, we performed in vitro transcript/translation experiments using the E. coli 30S lysate extract system (Promega) with increasing concentrations of AeaTMOF or Oncocin112 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). The latter was shown by X-ray crystallography to occupy the ribosomal exit tunnel at its entrance, blocking tRNA movement, mRNA translation, and protein biosynthesis [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We observed that AeaTMOF belongs to a family of proline-rich peptides that were shown to act as antimicrobial peptides by inhibiting the translation of proteins by bacterial ribosomes like Oncocin112 [13][14][15]. Therefore, we performed in vitro transcript/translation experiments using the E. coli 30S lysate extract system (Promega) with increasing concentrations of AeaTMOF or Oncocin112 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). The latter was shown by X-ray crystallography to occupy the ribosomal exit tunnel at its entrance, blocking tRNA movement, mRNA translation, and protein biosynthesis [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…To test the effect of AeaTMOF on the translation of larval Ae. aegypti late trypsin, the TnT T7 insect cell extract protein expression system from S. frugiperda Sf21 cell line (Promega) was incubated with different concentrations of AeaTMOF in a reaction mixture containing TNT T7 ICE master mix of 10 µL, pFA25A ICE T7 flexi-late larval Trypsin (0.45 µg/mL) (see Section 2.2) 0.5 µL, [3,4,5 3 H]Leucine 0.5 µL, AeaTMOF (0.01 to 1000 µM), and nuclease-free water to a total volume of 12.5 µL. The incubation mixtures were incubated at 30 • C for 4 h. At the end of the incubation period, aliquots (10 µL) were removed and spotted on filter paper squares (1 × 1 cm) and washed in cold 10% TCA for 10 min, and twice in cold 5% TCA for 5 min each followed by 2 min with ethanol (100%).…”
Section: Inhibition Of Larval Ae Aegypti Late Trypsin Translation In ...mentioning
confidence: 99%
See 3 more Smart Citations